Sunteți pe pagina 1din 14

9.

Beam on elastic foundations


9.1 Equations of the beam on elastic foundation

y, v

Figure 9.1: A beam on an elastic foundation.

Q q ( x)
M M + M ′Δx

r ( x) Q + Q′Δx

dx

Figure 9.2: The forces acting on a beam element on an elastic


foundation.

In addition to the distributed loading q ( x) a beam on elastic foundation


(Fig. 9.1) is loaded by foundation pressure r ( x) . For the vertical
condition of equilibrium of a differential beam element in Fig. 9.2, we get

Q + Q′dx − Q + qdx − rdx = 0 ⇒ (Q′ + q − r )dx = 0


(9.1)
⇒ Q′ = − q + r.

For its moment condition of equilibrium, we get

dx
M − M − M ′dx + Qdx + (q − r )dx ⋅ =0
2
≈0

dx
⇒ [− M ′ + Q + (q − r ) ]dx = 0 (9.2)
2
⇒ Q = M ′.

Rak-54.1300 Principles of structural mechanics, lecture notes 270


By combining results (9.1) and (9.2), we obtain the equilibrium equation
of a beam element on an elastic foundation

M ′′ = −q + r. (9.3)

This differs from the equation M ′′ = −q of a normal beam in that it has


the foundation pressure r . Other equations of normal bars are applicable
as such to beams on elastic foundations. Here we shall limit our study to
the elementary theory of bending and linear elastic beams. The most
essential other equations are then the relationship between rotation and
deflection

ϕ = v′ , (9.4)

the relationship between curvature and deflection

κ = −v′′ , (9.5)

the relationship between bending moment and curvature

M = EIκ , (9.6)

and the relationship between shear force and bending moment

Q = M ′. (9.7)

9.2 Foundation models


In addition to the equations above, we need a model of foundations,
which describes the relationship between the deflection v( x) of the beam
and the foundation pressure r ( x) .

The simplest and most commonly used foundation model is the so called
Winkler foundation (Winkler 1867). This model assumes that the
foundation pressure is directly proportional to deflection, i.e.

r ( x) = kv( x), (9.8)

where k is the so called foundation modulus.

Rak-54.1300 Principles of structural mechanics, lecture notes 271


v c

d d d d

Figure 9.3: The mechanical model of the Winkler foundation.

The Winkler foundation can be thought of as consisting of springs at


equal intervals as presented in Fig. 2.1. One spring acts on the beam with
a force R = cv , where c is the spring constant of the spring. Thus we get
k

R c
r= = v, (9.9)
d d

for the average foundation pressure and the modulus of foundation is then

c
k= . (9.10)
d

Fig. 9.4 illustrates the action of point load F on the Winkler foundation.
Only the spring situated at the point of action of force F contracts.
F

Figure 9.4: The action of a point load on the Winkler foundation.

Though the Winkler foundation is an extremely simple model of real


foundations, such as soil, it is widely used because of its simplicity.
Based on the Archimedean principle, we easily see that water acts as a
Winkler foundation for structures floating in it.

If we strive to model the actual behavior of foundations more


realistically, we must use more complicated models. The so called
Wieghart foundation could be thought of as the next step from the
Winkler foundation. (Wieghart 1922, Pasternak 1026). In this model, the
springs of the Winkler foundation are conjoined by an inelastic rope (cf.

Rak-54.1300 Principles of structural mechanics, lecture notes 272


Fig. 9.5). From here onwards, we will limit our study to Winkler
foundations.

Figure 9.5: The action of a point load on the Wieghart foundation.

9.3 Differential equation of the beam on elastic


foundation
The (already known) relationship between bending moment and
deflection follows from expressions (9.5) and (9.6).

M = − EIv′′ (9.11)

By inserting this relationship and the relationship (9.8) between the


deflection and the foundation pressure into equilibrium equation
Error! Reference source not found., we get

( EIv′′)′′ + kv = q. (9.12)

This is the differential equation of the beam on elastic foundation. In the


case of a uniform (EI = constant) beam, it gets the form

EIv (4) + kv = q (9.13)

This can be expressed as

q
v (4) + 4 β 4v = , (9.14)
EI

where

k
β=4 . (9.15)
4 EI

The general solution to differential equation (9.14) is

Rak-54.1300 Principles of structural mechanics, lecture notes 273


v( x) = v ( x) + v0 ( x) , (9.16)

where v ( x) is the general solution to the homogenous part of the equation

v (4) + 4 β 4v = 0 (9.17)

and v0 ( x) is one particular solution of the full equation (9.14).

The general solution to equation (9.17) can presented in two alternative


forms (cf. Mikkola Martti: Kimmoisalla alustalla oleva palkki, TKK,
Rakennetekniikan laitos, julkaisu 36, Otaniemi 1981).

v = e− β x ( B1 cos β x + B2 sin β x) + e β x ( B3 cos β x + B4 sin β x) , (9.18)

and

v ( x) = C1Y1 ( β x) + C2Y2 ( β x) + C3Y3 ( β x) + C4Y4 ( β x) , (9.19)

where the auxiliary functions Yi are

Y1 (ξ ) = cosh ξ cos ξ ,
1
Y2 (ξ ) = (cosh ξ sin ξ + sinh ξ cos ξ ),
2
1 (9.20)
Y3 (ξ ) = sinh ξ sin ξ ,
2
1
Y4 (ξ ) = (cosh ξ sin ξ − sinh ξ cos ξ ).
4

The derivatives of auxiliary functions (9.20) can be found in table 9.1 and
the following holds for these auxiliary functions:

Y1 (0) = 1, Y2 (0) = Y3 (0) = Y4 (0) = 0. (9.21)

Rak-54.1300 Principles of structural mechanics, lecture notes 274


Table 9.1: Derivatives of auxiliary functions Yi (ξ ) .

i Yi Yi′ Yi′′ Yi′′′ Yi (4)


1 Y1 −4Y4 −4Y3 −4Y2 −4Y1
2 Y2 Y1 −4Y4 −4Y3 −4Y2
3 Y3 Y2 Y1 −4Y4 −4Y3
4 Y4 Y3 Y2 Y1 −4Y4

The form of particular solution v0 ( x) is determined by the distributed


load q ( x) . Thus the equation v0 ( x) = 0 holds on the unloaded part of the
beam. If the distributed load q ( x) has a polynomial expression, whose
degree is not above three, a trial solution v0 ( x) of the same degree can
also be taken for it. v (4) ( x) = 0 , and insertion into differential equation
(9.14) then yields

q ( x)
4 β 4v0 ( x) = , (9.22)
EI

from which a result follows directly for the particular solution

q ( x) q ( x)
v0 ( x) = = . (9.23)
4 β EI
4
k

This simple expression of the particular solution holds, if the distributed


loading q ( x) is a polynomial, whose degree is not above three.

9.4 Semi-infinite solution to the beam on elastic


foundation
If the a beam on elastic foundation is long enough, i.e. if its length L
satisfies the condition
βL > 5, (9.24)

the edge disturbances caused by the supports of the bar ends or by the
point forces (and/or moments) are local enough to be solved without
taking the disturbances of the other edge into account. In these kinds of
cases, one can use the so called semi-infinite solution to the beam on
elastic foundation.

Rak-54.1300 Principles of structural mechanics, lecture notes 275


The semi-infinite solution to the beam on elastic foundation is obtained as
a sum of the general solution (9.18) to the homogenous equation and the
particular solution v0 ( x) . Let us place the origin x = 0 of our coordinate
system on the end of the beam under consideration. The beam is then
either on the side of the positive or the negative x axis.

If the beam is on the side of the positive x axis ( x ≥ 0 ), general solution


(9.18) must disappear, when x → ∞ . We get the conditions B3 = 0 and
B2 = 0 for the constants of integration. If the beam is on the side of the
negative x axis ( x ≤ 0 ), general solution (9.18) must disappear, when
x → −∞ . We get the conditions B1 = 0 and B2 = 0 for the constants of
integration. The results can be combined into a single formula

v = e ∓ β x (C1 cos β x + C2 sin β x) , (9.25)

where the upper sign corresponds to the positive x axis ( x ≥ 0 ) and the
lower sign to the negative x axis ( x ≤ 0 ). We then get a solution to the
problem in terms of the constants of integration

v( x) = e ∓ β x (C1 cos β x + C2 sin β x) + v0 ( x). (9.26)

Constants of integration C1 and C2 are determined using the boundary


conditions.

9.5 Finite solution to the beam on elastic foundation


When the length of the beam on an elastic foundation satisfies the
condition

βL < 5, (9.27)

one must use the so called finite solution to the beam on elastic
foundation. The finite solution to the beam on elastic foundation is
obtained as a sum of general solution (9.19) to the homogenous equation
and the particular solution v0 ( x) . The solution is then

v( x) = C1Y1 ( β x) + C2Y2 ( β x) + C3Y3 ( β x) + C4Y4 ( β x) + v0 ( x). (9.28)

Constants of integration C1 , C2 , C3 , and C4 are determined using the


boundary conditions.

Rak-54.1300 Principles of structural mechanics, lecture notes 276


9.5 Examples
Example 9.1: The beam on elastic foundation below is free at its left end and acted
on by point load P. The right end of the beam is far enough ( β L > 5 )
for the theory of the semi-infinite beam to be applied. Let us determine
the distributions of the deflection, bending moment, and shear force.

P
EI
x
x=0 k
L

Solution:

Deflection, bending moment, and shear force in terms of the constants of integration:

(Since the beam has no distributed load, the particular solution is v0 ( x) = 0. )

v( x) = e − β x (C1 cos β x + C2 sin β x)


v ′( x) = − β e − β x [(C1 − C2 ) cos β x + (C1 + C2 ) sin β x]
M ( x) ≡ − EIv ′′( x) = 2 EI β 2 e− β x (C2 cos β x − C1 sin β x)
Q( x) ≡ M ′( x) = 2 EI β 3 e − β x [−(C1 + C2 ) cos β x + (C1 − C2 ) sin β x]

Bending moment and shear force at the left end of the beam:

δ δ 1 δ P
M (δ ) = − P ⋅ δ + kv( )δ ⋅ = − Pδ + kv( )δ 2
2 2 2 2
δ → 0 ⇒ M (0) = 0 M (δ )
δ δ
Q(δ ) = − P + kv( )δ kv( )δ Q(δ )
2 2
δ → 0 ⇒ Q (0) = − P. δ ≈0

Note: As we can observe, the boundary conditions are the same as at the free end of a
regular beam, where a point load acts. The boundary conditions of beams on
elastic foundations are generally the same as boundary conditions of regular
beams.

Boundary conditions at the left end of the beam:

M (0) = 0, Q(0) = − P

Determining the constants of integration:

Rak-54.1300 Principles of structural mechanics, lecture notes 277


M (0) ≡ 2 EI β 2 C2 = 0 ⇒ C2 = 0
P
Q(0) ≡ −2 EI β 3 (C1 + C2 ) = − P ⇒ C1 =
2 EI β 3

Deflection, bending moment, and shear force:

P
v( x) = e − β x cos β x
2 EI β 3

P
M ( x) = − e − β x sin β x
β
Q( x) = Pe − β x (sin β x − cos β x)

Dimensionless expressions:

v( x) EI β 3 1 − β x
= e cos β x
P 2
M ( x) β
= −e − β x sin β x
P
Q( x)
= e − β x (sin β x − cos β x)
P

Deflection:

-0,1 0 1 2 3 4 βx 5
0
0,1
0,2
0,3
0,4
0,5
v( x) EI β 3
0,6
P
Bending moment:

-0,35
-0,3
-0,25
-0,2
-0,15
-0,1
-0,05 0 1 2 3 4 βx 5
0
0,05 M ( x) β
P

Rak-54.1300 Principles of structural mechanics, lecture notes 278


Shear force:

-1,2
-1
-0,8
-0,6
-0,4
-0,2 0 1 2 3 4 βx 5
0
0,2
0,4 Q ( x)
P

Rak-54.1300 Principles of structural mechanics, lecture notes 279


Example 9.2: The beam on an elastic foundation below is free at the ends and on its
left end acts a point load P. Let us determine the distributions of the
deflection, bending moment, and shear force, when k = 64 EI / L4 .

P
EI
x
x=0 k
L

Solution:

Constant β :

k 64 EI / L4 2
β= 4 =4 = ⇒ β L = 2 < 5 ⇒ Finite beam.
4 EI 4 EI L

Determining values of functions Yi with the value β L = 2 of the argument and using
the notation Yi ≡ Yi ( β L) :

Y1 ≡ Y1 ( β L) = cosh 2 cos 2 = −1,5656


1
Y2 ≡ Y2 ( β L) = (cosh 2sin 2 + sinh 2 cos 2) = 0,9558
2
1
Y3 ≡ Y3 ( β L) = sinh 2sin 2 = 1, 6489
2
1
Y4 ≡ Y4 ( β L) = (cosh 2sin 2 − sinh 2 cos 2) = 1, 2326
2

Deflection, bending moment, and shear force in terms of the constants of integration:

(Since the beam has no distributed load, the particular solution is v0 ( x) = 0. )

v( x) = C1Y1 ( β x) + C2Y2 ( β x) + C3Y3 ( β x) + C4Y4 ( β x)


M ( x) ≡ − EIv′′( x) = EI β 2 [4C1Y3 ( β x) + 4C2Y4 ( β x) − C3Y1 ( β x) − C4Y2 ( β x)]
Q( x) ≡ M ′( x) = EI β 3[4C1Y2 ( β x) + 4C2Y3 ( β x) + 4C3Y4 ( β x) − C4Y1 ( β x)]

Boundary conditions:

M (0) = 0, Q(0) = − P, M ( L) = 0, Q( L) = 0

Determining the constants of integration:

Rak-54.1300 Principles of structural mechanics, lecture notes 280


0 0 1 0

M (0) ≡ EI β [4C1 Y3 (0) + 4C2 Y4 (0) − C3 Y1 (0) − C4 Y2 (0)] = 0


2

⇒ − EI β 2C3 = 0 ⇒ C3 = 0

0 0 0 `1

Q(0) ≡ EI β 3 [4C1 Y2 (0) + 4C2 Y3 (0) + 4C3 Y4 (0) − C4 Y1 (0)] = − P


P
⇒ − EI β 3C4 = − P ⇒ C4 =
EI β 3
0 P /( EI β 3 )

M ( L) ≡ EI β [4C1Y3 ( β L) + 4C2Y4 ( β L) − C3 Y1 ( β L) − C4 Y2 ( β L)] = 0


2

P
⇒ 4C1Y3 + 4C2Y4 = Y2 =0
EI β 3
P
⇒ 1,6489C1 + 1, 2326C2 = 0,9558
4 EI β 3
0 P /( EI β 3 )

Q( L) ≡ EI β 3 [4C1Y2 ( β L) + 4C2Y3 ( β L) + 4 C3 Y4 ( β L) − C4 Y1 ( β L)] = 0


P
⇒ Y2C1 + Y3C2 = Y1
4 EI β 3
P
⇒ 0,9558C1 + 1, 6489C2 = −1,5656
4 EI β 3

⎡1, 6489 1, 2326 ⎤ ⎧ C1 ⎫ P ⎧ 0,9558 ⎫


⇒ ⎢ ⎥ ⎨ ⎬= 3 ⎨ ⎬
⎣ 0,9558 1, 6489 ⎦ ⎩C2 ⎭ 4 EI β ⎩−1,5656 ⎭
⎧ C ⎫ ⎧ 0,5688 ⎫ P
⇒ ⎨ 1⎬ = ⎨ ⎬
⎩C2 ⎭ ⎩−0,5671⎭ EI β
3

The result is:

P P P
C1 = 0,5688 , C2 = −0,5671 , C3 = 0, C4 =
EI β 3
EI β 3
EI β 3

Deflection, bending moment, and shear force:

P
v( x) = [0,5688Y1 ( β x) − 0,5671Y2 ( β x) + Y4 ( β x)]
EI β 3
PL3 x x x
= [0, 0711Y1 (2 ) − 0, 0709Y2 (2 ) + 0,125Y4 (2 )]
EI L L L
P
M ( x) = EI β 2 ⋅ [4 ⋅ 0,5688Y3 ( β x) − 4 ⋅ 0,5671Y4 ( β x) − Y2 ( β x)]
EI β 3
x x x
= PL[1,1376Y3 (2 ) − 1,1342Y4 (2 ) − 0,5Y2 (2 )]
L L L

Rak-54.1300 Principles of structural mechanics, lecture notes 281


P
Q( x) ≡ M ′( x) = EI β 3[4 ⋅ 0,5688Y2 ( β x) − 4 ⋅ 0,5671Y3 ( β x) − Y1 ( β x)]
EI β 3
x x x
= P[2, 2752Y2 (2 ) − 2, 2684Y3 (2 ) − Y1 (2 )]
L L L

Corresponding dimensionless expressions:

v( x) EI x x x
3
= 0, 0711Y1 (2 ) − 0, 0709Y2 (2 ) + 0,125Y4 (2 )
PL L L L
M ( x) x x x
= 1,1376Y3 (2 ) − 1,1342Y4 (2 ) − 0,5Y2 (2 )
PL L L L
Q( x) x x x
= 2, 2752Y2 (2 ) − 2, 2684Y3 (2 ) − Y1 (2 )
P L L L

Rak-54.1300 Principles of structural mechanics, lecture notes 282


Deflection:

-0,04
x
-0,02 0 0,2 0,4 0,6 0,8 L 1
0

0,02
0,04

0,06
0,08 v( x) EI
PL3

Bending moment:

-0,16
-0,14
-0,12
-0,1
-0,08
-0,06
-0,04 x
-0,02 0 0,2 0,4 0,6 0,8 L 1
0
0,02 M ( x)
PL
Shear force:

-1,2
-1
-0,8
-0,6
-0,4 x
-0,2 0 0,2 0,4 0,6 0,8 1
L
0
0,2
0,4
Q( x)
P

Rak-54.1300 Principles of structural mechanics, lecture notes 283